2022
DOI: 10.1136/thorax-2022-218702
|View full text |Cite
|
Sign up to set email alerts
|

Web-based physical activity promotion in young people with CF: a randomised controlled trial

Abstract: BackgroundPhysical activity levels are known to decline following hospitalisation for people with cystic fibrosis (pwCF). However, optimal physical activity promotion strategies are unclear. This study investigated the effect of a web-based application (ActivOnline) in promoting physical activity in young pwCF.MethodsMulticentre randomised controlled trial with assessor blinding and qualitative evaluation. People with CF (12–35 years) admitted to hospital for a respiratory cause were eligible and randomised to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 41 publications
0
15
0
Order By: Relevance
“…In light of the improvements in the overall health status of pwCF, investigating the role of physical activity and exercise is timely and desired by the CF community 3. Two papers in this issue of Thorax focus on physical activity and exercise in pwCF, respectively, either as a substitute for traditional ACT or as an intervention to promote physical activity 4 5…”
mentioning
confidence: 99%
See 4 more Smart Citations
“…In light of the improvements in the overall health status of pwCF, investigating the role of physical activity and exercise is timely and desired by the CF community 3. Two papers in this issue of Thorax focus on physical activity and exercise in pwCF, respectively, either as a substitute for traditional ACT or as an intervention to promote physical activity 4 5…”
mentioning
confidence: 99%
“…In the second paper, Cox et al 5 reported on the effects of a 12-week web-based randomised controlled trial (RCT) using elements of behaviour change theory in pwCF with a 6 months follow-up. Study participants were recruited during hospital admission for a pulmonary exacerbation across eight CF centres in Australia.…”
mentioning
confidence: 99%
See 3 more Smart Citations